Memaksimalkan Kinerja Karyawan Bank BNI Kantor Cabang Utama Yogyakarta melalui Sinergi Pendidikan dan Pelatihan, Motivasi, Serta Kompensasi - Mursyid, Mursyid; Siyamto, Yudi; Herlambang, Susatyo (FEB Universitas Maritim Semarang, 2024)
This study aims to analyze the impact of education and training, motivation, and compensation on employee performance at Bank BNI Main Branch Yogyakarta. A quantitative method using survey and multiple linear regression analysis was employed. A sample of 75 respondents was selected using Slovin's formula from a population of 238 employees. The results indicate that all three variables significantly affect employee performance. Education and training enhance employee skills, while motivation drives employees to commit more to their work. Fair and competitive compensation contributes to employee satisfaction and productivity. This study provides valuable insights for organizations in developing employee-related policies. However, the research is limited to a single branch and employs a quantitative approach, suggesting the need for further studies with a qualitative approach and a broader sample size for more comprehensive results.